INVESTIGATION OF ACCRETION DISK INSTABILITY IN BLACK HOLE X-RAY TRANSIENT THROUGH ANALYSIS OF THE X-RAY LIGHT CURVE AND SPECTRAL VARIABILITY - Andamari Saraswati, Tiara
One of the Black Hole X-ray Transient (BHXT) with the largest black hole mass and longest orbital period in the Galaxy, GRS 1915+105, has been active for 26 years since its discovery in 1992 and has been observed several times in the super-Eddington state before entering quiescent in 2018. Aside from the long-term variability found in another BHXT, GRS 1915+105 also exhibits short-term variability transition in its light curve and spectra which has never been seen before in another BHXT. In this study, we will examine the short-term variability pattern in the light curve and spectra of GRS 1915+105 and several other ‘normal’ BHXTs in our sample using NuSTAR archival data (2012–2024) in 3–20 keV range. From the results, we will analyze the physical conditions of the accretion disk of GRS 1915+105 during the flaring (2012–2018) and quiet (2018–2024) phase. Aside from that, we will also analyze the difference in variability type between GRS 1915+105 and other BHXTs in our sample. In the NuSTAR data (2012–2024), six classical variability classes were detected (?, ?, ?, ?, ?, and ?) and one new additional class which we called ? class. Spectra which coincides with the ? and ? are representing the standard disk. Meanwhile, the presence of several class which we called states group 2 are the signs of an increased advection rate which means that the disk transitioned into a slim disk. This transition occurs at luminosity ? 0.5 LEdd for GRS 1915+105. Aside from GRS 1915+105, 4U 1543–475 also showed signs of increased advection rate with transition luminosity at ? 0.6 LEdd. The difference between the flaring (2012–2018) and quiet (2018–2024) phase of GRS 1915+105, aside from not showing any shortterm variability transition, is the characteristic of its local and neutral absorption component. This component has a varying covering fraction during the flaring phase but increased dramatically along with an increase in the hydrogen column density (NH) when transitioned into the quiet phase. The quiet phase is dominated by typical hard state spectra except for those that correspond with what we suspected as mini-outburst, which shows thermal state spectra. From the analysis of the Xray light curve and spectra, there are strong indications that GRS 1915+105 is not entering quiescent yet, but is covered by the local absorption component which in turn decreases the amount of X-ray photons received by the observer drastically.